CAD conceptual design of an oil palm seedling transplanter - El Pebrian, Darius; Yahya, Azmi (Universiti Putra Malaysia, 1999)
A conceptual design of an oil palm seedling transplanter was developed using AutoCAD R14 software. This seedling transplanter consists of the main chassis, seedling bin, conveying unit, seedling placement assembly and its associated hydraulic control unit. The transplanter is to be trailed from a 4-wheel tractor having at least 70 hp (52 kW) engine size. It is equipped with a seedling bin that could accommodate 28 oil palm seedlings per operating trip. Two operators are required in the involved transplanting operation; a driver for the tractor and an operator for transplanter. The driver drives the tractor-transplanter combination in the field, while the operator operates the hydraulic control system of the transplanter to integrate all operational activities. The involved operational activities include the preparations of planting hole, placement of seedling in the prepared hole, covering of the seedling in the prepared hole, and compacting of the soil around the planted seedling.